Pemetaan Sistematis Faktor-Faktor Penentu Pencegahan Fraud dalam Pengelolaan Dana Desa di Indonesia - Aditiyanto Ekaputra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to systematically map the determinants of fraud prevention in village fund management in Indonesia based on the findings of previous empirical research. The method used is a Systematic Literature Review (SLR) with reference to the PRISMA protocol through a search of scientific articles published in the 2015–2025 period based on Google Scholar. The scientific articles were then selected based on predetermined inclusion and exclusion criteria to obtain ten relevant empirical articles for analysis. The results of the study indicate that the Government Internal Control System (SPIP) and the competence of village officials are the most dominant and consistent factors in preventing village fund fraud. Other supporting factors include individual morality and ethics, transparency and accountability, community participation, and a whistleblowing system that plays a role in strengthening the effectiveness of internal control through social supervision and increasing integrity. These findings confirm that preventing village fund fraud requires an integrated approach that integrates control systems, governance and individual behavior and is aligned with national policies such as the Village Law, SPIP, and Siskeudes to realize transparent, accountable, and sustainable village financial management.